Large insertion in radish GRS1 enhances glucoraphanin content in intergeneric hybrids, Raphanobrassica (Raphanus sativus L. x Brassica oleracea var. acephala) - Endo, Ryota; Chikano, Hiroshi; Itabashi, Etsuko; Kawasaki, Mitsuyo; Ohara, Takayoshi; Kakizaki, Tomohiro (Frontiers in Plant Science, 2023)
Glucosinolates (GSLs), precursors of isothiocyanates (ITCs), are present in Brassicaceae plants have been found to have health benefits. Sulforaphane (4-(methylsulfinyl)butyl ITC) is an ITC stored in the form of 4-(methylsulfinyl)butyl GSL (glucoraphanin, 4MSOB) in Brassica vegetables, such as broccoli and kale. Sulforaphane activates Nrf2 expression, a transcription factor responsible for inducing physiological activities such as detoxification in the human body, and it represents a functional component unique to cruciferous vegetables. Raphanobrassica is an inter-generic hybrid between radish and kale, and it contains a high amount of 4MSOB. However, Raphanobrassica contains as much 4-methylsulfinyl-3-butenyl GSL (glucoraphenin, 4MSO3B) as it does 4MSOB. GLUCORAPHASATIN SYNTHASE 1 (GRS1) is an enzyme present in radish that synthesizes 4-methylthio-3-butenyl GSL (glucoraphasatin, 4MT3B), a precursor of 4MSO3B, using 4-(methylthio)butyl GSL (glucoerucin, 4MTB) as a substrate. Since the precursor of 4MSOB is also 4MTB, it was considered that both 4MSOB and 4MSO3B accumulate owing to competition in Raphanobrassica. We hypothesized that owing to the impaired function of GRS1 in Raphanobrassica, it may be possible to breed Raphanobrassica cultivars containing a high 4MSOB content. In this study, we generated Raphanobrassica populations with functional and defective GRS1 and compared the GSL composition in the two populations using high-performance liquid chromatography. The mean 4MSOB content in leaves of the defective-type populations was higher than that in the functional-type population, and the defective/functional ratio ranged from 2.02 to 2.51-fold, supporting this hypothesis. Furthermore, leaves, flower buds, stems, and roots contained higher amounts of 4MSOB in the defective population than in the functional population. The leaf 4MSOB content of defective Raphanobrassica grown in this study was comparable to that of previously studied vegetables (such as broccoli sprouts) with high 4MSOB content. Raphanobrassica with defective GRS1 represents a new leafy vegetable with high 4MSOB content which exhibits anti-cancerous and anti-inflammatory potentials.